Fracture Resistances of Cast Metal and Ceramic Dowel and Core Restorations: A Pilot Study - Emine Yal¸cın, DDS;1 Murat C. C¸ehreli, DDS, PhD;1 (Journal of Prosthodontics, 2005)
The purpose of this study was to compare fracture strengths of teeth restored with cast metal and ceramic dowel and cores supporting all-ceramic crowns.